The Analysis of Student Demonstration Actions Against RUU KUPH and RUU KPK: Between Critical and Narcissistic Attitudes (JED (Jurnal Etika Demokrasi), 2020)
Abstract. Various policies issued by the legislative and executive bodies provoke various demonstrations carried out by students in various regions in Indonesia. This demonstration is a form of student attention in the sustainability of the Indonesian state. There are differences in the nuances of the demonstration that were conducted by students a few decades ago and now. The demonstration is now more a place for student narcissism. This study aims to analyze the students' critical and narcissistic attitudes in demonstrations. The research approach uses descriptive qualitative. Retrieval of data through interviews, observation and documentation. The research phase includes pre-field, field and data analysis. The location of the study was at the University of Mataram Elementary School Teacher Education Study Program. The data sources are students in the 3rd and 5th semester and lecturers at the University of Mataram, Elementary School Teacher Education Program. The results showed: (1) The demonstration was triggered by students' objections to the RUU KPK and the RUU KUHP. (2) Demonstrations bring positive and negative impacts for students. (3) There was a change in the nuances of the demonstration conducted by students. If all this time the demonstration was identical with the criticism of students, but now it has developed into a narcissism arena. (4). Student narcissism in demonstrations is based on their obsession to get recognition and appreciation from the community.Keywords: demonstration, critical, narcissismAbstrak.  Berbagai kebijakan yang dikeluarkan oleh lembaga legislatif dan eksekutif memancing berbagai aksi demonstrasi yang dilakukan oleh mahasiswa di berbagai daerah di Indonesia. Aksi demonstrasi ini merupakan wujud perhatian mahasiswa dalam keberlangsungan negara Indonesia. Terdapat perbedaan nuansa demonstrasi yang dilakukan mahasiswa beberapa dekade yang lalu dengan sekarang. Demonstrasi saat ini lebih banyak dijadikan ajang narsisme mahasiswa. Penelitian ini bertujuan untuk menganalisis sikap kritis dan narsis mahasiswa dalam aksi demonstrasi. Pendekatan penelitian menggunakan kualitatif deskriptif. Pengambilan data melalui wawancara, observasi dan dokumentasi. Tahap penelitian meliputi pra lapangan, lapangan dan analisis data. Lokasi penelitian di Program Studi Pendidikan Guru Sekolah Dasar Universitas Mataram. Sumber data yakni mahasiswa semester 3 dan 5 dan dosen Program Studi Pendidikan Guru Sekolah Dasar Universitas Mataram. Hasil penelitian menunjukkan: (1) Aksi demonstrasi dipicu oleh keberatan mahasiswa terhadap RUU KPK dan RUU KUHP. (2) Aksi demonstrasi membawa dampak positif dan negatif bagi mahasiswa. (3) Terjadi perubahan nuansa demonstrasi yang dilakukan oleh mahasiswa. Jika selama ini aksi demonstrasi identik dengan kekritisan mahasiswa, namun saat ini berkembang menjadi ajang narsisme. (4). Sikap narsisme mahasiswa dalam demonstrasi didasari oleh obsesi mereka untuk mendapatkan pengakuan dan penghargaan dari masyarakatKata Kunci: demonstrasi, kritis, narsis